Sistem Informasi Panggil Kuli Proyek Berbasis Website (SIPAKUPROY) - Waeisul Bismi; Anisa Febriyani; Farid Ramadhan (Universitas Komputer Indonesia, 2023)
In the current global changes, there are also impacts, such as the difficulty in finding experienced and trustworthy construction workers. However, the current development of web-based information systems brings significant benefits in various job aspects, including distance, time, and accessibility. This encourages the construction industry to utilize technology, systems, and information to provide more efficient and easily accessible services to the public. Confronting these challenges, the SIPAKUPROY platform was created as a solution. Its goal is to facilitate the search for reliable and experienced construction workers through a digital platform. The analysis during the creation of this platform revealed several issues, especially in transitioning from a manual bidding system to a digital one. This transition process is supported by the waterfall model research method, as well as an analysis of reliable software and hardware needs. System design also includes the creation of a database using Logical Record Structured (LRS) and Entity Relationship Diagram (ERD), along with a user-friendly design interface. This process is carried out in an effort to design the web-based project labor calling information system (SIKUPROY). The entire sequence of designing and creating the SIPAKUPROY platform aims to provide convenience to individuals who want to build houses but feel uncertain due to a lack of connections or relationships with construction workers. Through this platform, the process of finding and selecting construction workers is expected to become more reliable, efficient, and aligned with the community's needs. Key Words: Construction workers, System Information, Website